Можливості виявлення оперативно-тактичних та тактичних безпілотних літальних апаратів - Сергієнко, В. А. (ХНУРЕ, 2021)
The main problem with radar detection of operational-tactful and tactful UAVs є їх small radio-locating unit is so small, so for the detection of such lithal devices, the necessary radio-locating devices are required with a high energy potential. Such a potential of the RTV radar may not be possible, but the ways of doing it in case of flight detection at a distance of hundreds of kilometers and UAVs at ranges of 10.
Keywords: БПЛА; радіолокація